Studies on paddy land used changes area for distribution crop fertilizer management under Lembaga Kemajuan Pertanian Muda [MADA] administration in Arau Perlis / Mohd Sallehuddin Mohd Zali - Mohd Zali, Mohd Sallehuddin (2019)
This study was carried out to determine the area of land use which was registered under MADA management. Registration of land use is an important part for MADA administration. This is because land use registration is to manage all matters relating to agricultural management of land. In this study, to overcome the problem faced by the Muda Agricultural Development Authority to find out the land use area that has register in MADA management. The study area is in the area of Region 1 which involves at PPKA1 Guar Sanji Arau Perlis Area. In this study, the number of samples lot has selected by the MADA involved 21 lots. Data used in this study are data from online base map GIs, data NDCDB and fertilizer records to the sample lot. . The purpose of this study was to determine the extent of rice land use to validate the management of fertilizer distribution plants in MADA area by using GIs application. The methodology has use to obtain the aim in this study using the ArcGIS software to identify land use in selected sample lot. By using the land use analysis method for the selected sample lot can be made accurately. In the end of study has shown the land use map for sample lot for PPKA1. From this study is to help MADA administration in determination land use area for paddy field and for distribution crop fertilizer.